Screening of Vietnamese medicinal plants for NF-κB signaling inhibitors: Assessing the activity of flavonoids from the stem bark of Oroxylum indicum. (15th January 2015) - Tran, Thi Van Anh; Malainer, Clemens; Schwaiger, Stefan; Hung, Tran; Atanasov, Atanas G.; Heiss, Elke H.; Dirsch, Verena M.; Stuppner, Hermann
Abstract: Ethnopharmacological relevance: Seventeen plants used in Vietnamese traditional medicine for the treatment of inflammatory disorders were screened for NF-κB inhibitory activity. Oroxylum indicum, which exhibited activity, was investigated in detail. Materials and methods: Forty plant extracts from 17 species were prepared by maceration using dichloromethane and methanol and were tested (10 µg/mL) to evaluate their ability to inhibit NF-κB activation using TNF-α-stimulated HEK-293 cells stably transfected with a NF-κB-driven luciferase reporter. The active extract of Oroxylum indicum was subsequently fractionated by different chromatographic techniques. After isolation, all single compounds were identified by spectroscopic methods and assessed for NF-κB inhibitory effects. Results: The dichloromethane extracts obtained from Chromolaena odorata leaves and the stem bark of Oroxylum indicum showed distinct inhibitory effects on NF-κB activation at a concentration of 10 µg/mL. The active extract of Oroxylum indicum was subjected to further phytochemical studies resulting in identification of four flavonoid aglyca and six flavonoid glycosides. Pharmacological evaluation of the obtained compounds identified oroxylin A as the most active substance (IC50 =3.9 µM, 95% CI: 3.5–4.4 µM), while chrysin and hispidulin showed lower activity with IC50 =7.2 µM (95% CI: 6.0–8.8 µM) and 9.0 µM (95% CI: 7.9–10.2 µM), respectively. Interestingly, in this study the activity of baicalein (IC50 =28.1 µM, 95% CI: 24.6–32.0 µM) was weak. The isolated glycosides showed no inhibitory activity when tested at a concentration of 30 µM. Quantification of the four active flavonoids in extracts and plant materials suggested that oroxylin A contributes to the NF-κB inhibitory activity of the stem barks of Oroxylum indicum to a greater extent than baicalein which was thought to be responsible for the anti-inflammatory activity of this plant. Conclusions: The screening presented in this study identified the dichloromethane extracts of Chromolaena odorata and Oroxylum indicum as promising sources for NF-κB inhibitors. Hispidulin, baicalein, chrysin and oroxylin A, isolated from Oroxylum indicum, were identified as inhibitors of NF- κB activation. Graphical abstract: